Determinants of Oral Diseases in the African and Middle East Region. (July 2015) - Chidzonga, M.M.; Carneiro, L.C.; Kalyanyama, B.M.; Kwamin, F.; Oginni, F.O.
Oral health policies must be developed that emphasize the role of social determinants in health and oral diseases. The aim of this report is to review literature on determinants of oral diseases and apply the concepts to promoting oral health in the African countries in the African and Middle East region (AMER). Structural and proximal determinants of oral diseases are common to those affected by other noncommunicable diseases (NCDs). Oral diseases are also heavily affected by issues of politics, poor health behaviors, underdeveloped health systems, and low oral health literacy. Wide-scale poverty exists in populations in the AMER. Oral health promotion and preventive oral health programs should therefore be integrated with those for general health and use the common risk factor approach (CRFA). Attempts should be made to improve the daily living conditions and reduce the incline of the social gradient. Oral health practitioners should use the CRFA when dealing with determinants of oral diseases and in the design of preventive oral health programs. The detrimental effects of the social determinants of health may be ameliorated by involving both the individual and community. Interventions in health promotion programs in the AMER need more research on the epidemiology of oral diseases and the role played by the social determinants of oral diseases, especially with regard to poverty. The high levels of poverty and low gross domestic product in most countries in the African region make it difficult to fund high-quality, affordable, accessible oral health services.